Paracrine and autocrine factors in the differentiation of the cumulus-oocyte complex - Buratini, J.; Caixeta, E. S. (Brazilian Coll Animal Reproduction, 2012)
A better understanding of the paracrine and autocrine regulatory loops within the cumulus-oocyte complex (COC) is fundamental for the improvement of in vitro maturation (IVM) outcomes in humans and domestic species. This review presents the most important local regulators identified in the COC to date with special attention to those secreted by the oocyte and acting on cumulus cells, as well as their roles in different processes crucial for the successful maturation of the COC. An autocrine regulatory loop mediated by epidermal growth factor-like (EGF-like) peptides in cumulus cells triggers COC maturation. During COC differentiation, oocyte secreted factors (OSFs), particularly members of the transforming growth factor-beta (TGF beta) and fibroblast growth factor (FGF) families, regulate meiotic resumption, cumulus expansion, cumulus metabolism, apoptosis and steroidogenesis.